2005
DOI: 10.1001/archopht.123.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Self-management of Age-related Macular Degeneration at the 6-Month Follow-up

Abstract: To assess the effectiveness at the 6-month follow-up of an age-related macular degeneration (AMD) selfmanagement program consisting of health education and enhancement of problem-solving skills in improving quality of life as shown by measures of mood and function. Methods: Six-month follow-up data were analyzed from 214 of 252 older adult volunteers (mean age, 80.8 years) with advanced AMD who had been randomly assigned to a 12-hour self-management program (n = 82), a series of 12 hours of tape-recorded healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(142 citation statements)
references
References 28 publications
6
133
1
2
Order By: Relevance
“…The regression test revealed that preoperative self-efficacy could explain four percent of the variance of depression after the surgery. Another study revealed that increased self-efficacy leads to less stress, better performance, and lower depression in the elderly suffering from macular degeneration (48). The findings of the current research are in accordance with the results of Bandura et al, Ogunyemi and Mabekoje, Schwartzer and Fuchs, and Schwarzer and Luszczynska, which found a positive relationship between self-efficacy and anxiety and depression (49)(50)(51)(52).…”
Section: Discussionsupporting
confidence: 90%
“…The regression test revealed that preoperative self-efficacy could explain four percent of the variance of depression after the surgery. Another study revealed that increased self-efficacy leads to less stress, better performance, and lower depression in the elderly suffering from macular degeneration (48). The findings of the current research are in accordance with the results of Bandura et al, Ogunyemi and Mabekoje, Schwartzer and Fuchs, and Schwarzer and Luszczynska, which found a positive relationship between self-efficacy and anxiety and depression (49)(50)(51)(52).…”
Section: Discussionsupporting
confidence: 90%
“…Brody et al found that a 12-hour self-management session reduced emotional distress over a 6-month period in AMD patients, 34 while Rovner et al found that six problem-solving treatment sessions resulted in a lower 2-month incidence rate of depressive symptoms but that these results were not maintained by 6 months. 35 Further research on interventions to prevent depression in patients with eye disease is warranted and should consider strategies to alleviate mobility limitation.…”
Section: Discussionmentioning
confidence: 99%
“…41,48,49 Self-management programs are becoming increasingly popular, adopting a group-based approach, with the aim of helping participants to take control in managing the consequences of visual impairment and developing problem solving skills through sharing experiences and coping strategies. 22,23,60,109,114 Given the wealth of different strategies employed in providing vision rehabilitation, there is a real need for evidence-based studies evaluating the effectiveness and cost-effectiveness of the various types of rehabilitation.…”
Section: B Vision Rehabilitation Servicesmentioning
confidence: 99%